The effect of using illustrated alphabet card media on first-grade students’ letter recognition ability at UPT SD Negeri No. 74 Bontorita II - ., Syamsuriyanti; Fauziah, Sitti Nurul; Asis, Ayu Alfira (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to evaluate the effect of using illustrated letter cards on the letter recognition ability of first-grade elementary school students. The research employed an experimental method with a pretest-posttest control group design. The subjects consisted of first-grade students who were divided into an experimental group and a control group. The experimental group received instruction using illustrated letter cards, while the control group was taught using conventional classroom methods. The results show that the use of illustrated letter cards significantly improved students’ letter recognition skills through visual stimulation, engaging learning activities, and more appealing letter recognition exercises. However, variations in learning outcomes among several students indicate the need for additional approaches for those experiencing difficulties. Based on the findings, it can be concluded that illustrated letter cards are an effective instructional medium for enhancing letter recognition skills in first-grade elementary school students.